Vapor-liquid equilibrium measurements and models for the ternary mixtures of R1234yf + R32 + R125 and R1234yf + R32 + CO2. (February 2023) - Peng, Shuzhou; Wang, Erqi; Li, Shuhao; Yang, Zhen; Duan, Yuanyuan
Highlights: First reported the VLE data of R1234yf + R32 + R125 ternary mixture. Provided new VLE data for the R1234yf + R32 + CO2 ternary mixture. New ternary mixtures model also well describes VLE properties of the binary mixtures. The PR + WS + NRTL model shows excellent performance. Abstract: R1234yf as the environmental friendly refrigerant has a low volumetric refrigeration capacity and light flammability. The refrigerant mixtures are expected to achieve excellent thermophysical performance, safety and environmental performance. The vapor-liquid equilibrium (VLE) is one of the most important properties of the mixtures. In this work, the VLE property of R1234yf + R32 + R125 and R1234yf + R32 + CO2 ternary mixtures were measured along 5 isotherms from 273.15 K to 313.15 K by a recirculation analytical apparatus. The Peng-Robinson (PR) equation of state combined with the van der Waals (vdW) mixing rule (PR + vdW), as well as the PR equation of state combined with the Wong-Sandler (WS) mixing rule and the non-random two-liquid (NRTL) activity coefficient model (PR + WS + NRTL) were used to correlate the VLE data. The model parameters were temperature-dependent and could describe the VLE properties of the ternary and binary subsystems. The results showed that the PR + WS + NRTL model was better than the PR + vdW model. The average absolute relative deviation of pressure (AARD( p )) and average absolute deviation of compositions (AAD( y )) of the PR + WS + NRTL model were 0.4% and 0.003 for R1234yf + R32 + R125 ternary mixture, and were 0.7% and 0.007 for R1234yf + R32 + CO2 ternary mixture. Experimental results and model calculations showed that both the ternary mixtures were zeotropic.